USER GENERATED CONTENT DAN DAYA TARIK VISUAL DALAM KEPUTUSAN PEMBELIAN FASHION LOKAL TIKTOK SHOP - Sobar, Agus; Setiadi, Sandi (REUGREUG: Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2025)
The purpose of this study is to determine the influence of User Generated Content and Visual Content Appeal on Purchase Decisions of local fashion products on TikTok Shop by Tokopedia. Social media has become an effective means of digital marketing, especially TikTok, which combines entertainment and e-commerce features. This study uses a quantitative methodology with an associative approach and involves 96 respondents who are active TikTok users and have purchased local fashion products through TikTok Shop by Tokopedia. The data was analyzed using multiple linear regression with the assistance of SPSS version 25. The results show that both partially and simultaneously, User Generated Content and Visual Content Appeal have a positive and significant effect on Purchase Decisions. The coefficient of determination value of 71.1% indicates that the two independent variables have a considerable contribution in explaining consumer purchase decisions. This research provides important implications for local fashion business players to further maximize digital content strategies through user reviews and appealing visual displays on social media. Keywords: User Generated Content, Visual Content Appeal, Purchase Decision